The effect of 'Out of hours surgery Service' in Israel on hip fracture fixation outcomes: a retrospective analysis - Yaniv Keren; Sybil Sailofsky; Doron Keshet; Michal Barak (BMC, 2017)
Abstract Background 'Out of Hours Surgery Service' (OHSS) was implemented in Israel, amongst other reasons, in order to reduce the time interval between hospital admission and surgery and consequently improve outcomes. The OHSS is currently operated in the public hospitals in Israel. In this study we compared the data of patients before and after OHSS implementation to determine its efficacy in improving patient care. Methods This is a retrospective observational study of 792 adult patients who underwent hip fracture surgery between 2002 and 2007 in a single hospital. The study population included two groups: patients that were operated before the implementation of the OHSS (2002-2004) and after the implementation of the OHSS (2005-2007). Data regarding all patients was collected using the institution's computer program. The following variables were analyzed: patients' demographics, time interval from hospitalization to surgery, causes for delaying surgery, post-operative length of hospitalization and mortality. Results Patients in the post-OHSS group had more illnesses and higher ASA classification than those in the pre-OHSS group. The post-OHSS group had a significantly decreased length of stay in the hospital before and after the surgery. After adjusting for ASA score and age, the post-OHSS group was found to have decreased post-operative hospitalization and lower post-operative mortality. Surgery was delayed in pre-OHSS period mainly due to operating rooms unavailability. Conclusion Implementation of OHSS facilitated operating room availability, thus early operation and reduced post-operative mortality. In accordance with other studies, patient's outcome is greatly influenced by the time from admission to hip fracture surgery.